PENGARUH BI 7-DAY REPO RATE, KURS USD-IDR, PRICE TO BOOK VALUE (PBV), DAN CADANGAN DEVISA INDONESIA TERHADAP RETURN PADA INDEKS INFOBANK15 - Endang Sri Apriani; Zilal Hamzah; Eleonora Sofilda (Media Ekonomi, 2020)
The Infobank Index15 is an index issued by the infobank magazine publisher itself, PT Infoartha Pratama. This index contains 15 banking stocks that have been listed on the Indonesian stock exchange, sorted by good fundamental criteria and relatively high liquidity. This study was conducted to determine and analyze the influence of macroeconomics on the Infobank Index15 on a monthly time series from 2013 to 2018, so the data can be said to be long-term, because that is the analytical tool used, VAR (Vector Auto Regression) / VECM. The findings of this study states that the BI 7 Day Repo Rate, USD-IDR EXCHANGE rate, and PBV have a negative siginificakt effect while Indonesia's foreign exchange reserves has insignificant effect on the Infobank Return Index15. Simultaneously the research variables have a siginificant affect the Infobank Return Index15.